2020
DOI: 10.4103/ijnm.ijnm_145_19
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen-expressing hepatic lesion: Metastatic or hepatocellular carcinoma

Abstract: Prostate-specific membrane antigen (PSMA) is a glycosylated type-II transmembrane protein highly expressed in certain tumor cells. It has emerged as a novel radiotracer for evaluation of prostate cancer. Increased PSMA expression in isolated liver lesion is a diagnostic challenge. Solitary liver metastasis from prostate cancer is rare. On the other hand, PSMA avid primary hepatocellular carcinoma (HCC) has been reported in literature. We report a case of PSMA expressing atypical HCC with normal alphafeto prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The only PSMA-expressing lesion is seen in the liver. No other PSMA expressing disease was observed in the scan (Das et al, 2020).…”
Section: Liver Cancermentioning
confidence: 85%
“…The only PSMA-expressing lesion is seen in the liver. No other PSMA expressing disease was observed in the scan (Das et al, 2020).…”
Section: Liver Cancermentioning
confidence: 85%
“…[ 68 Ga]Ga-PSMA-11 was recently introduced for the PET/CT imaging of patients with prostate cancer, but incidental uptake has been described in other cancers, including reports on HCC [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Since PSMA expression is associated with poor prognosis, the results of [ 68 Ga]Ga-PSMA PET/CT have strong clinical implications [11]. However, to date, the use of [ 68 Ga]Ga-PSMA PET/CT (mainly PSMA-11) for the diagnosis of HCC has only been reported in two studies [12,13] and several case reports [14][15][16][17][18]. Therefore, this study aimed to evaluate the feasibility of PET/CT imaging with [ 68 Ga]Ga-PSMA-11 in HCC and its impact on patient management.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of HCC shows high levels of PSMA expression on tumor vessels and on canalicular membrane of cells [26,28] and therefore important implications for PSMAtargeted imaging and therapy arise. PSMA-targeted imaging of HCC in clinical practice has been evaluated only by a few studies and most of these studies are case reports [22,23,[27][28][29][30][31][32][33][34], probably because of the small number of centers that currently use radiolabelled PSMA PET/CT or PET/ MRI, resulting in a reduction of the population of patients overall studied.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 55 articles were extrapolated with the computer literature search and by reviewing the titles and abstracts 43 of them were excluded because the reported data were not within the field of interest of this review. Twelve articles were selected and retrieved in full-text version [22][23][24][25][26][27][28][29][30][31][32][33]; one additional study was found screening the references of these articles [34]. A total of 13 articles were then included in the systematic review [22][23][24][25][26][27][28][29][30][31][32][33][34] (Fig.…”
Section: Literature Searchmentioning
confidence: 99%